2018
DOI: 10.29312/remexca.v2i5.1615
|View full text |Cite
|
Sign up to set email alerts
|

VARIACIÓN EN LA TOLERANCIA A DESINFECTANTES DE GENOTIPOS ÉLITE DE Coffea spp. CULTIVADOS in vitro

Abstract: La embriogénesis somática puede ser afectada por la oxidación de los explantes al aplicar un método común de desinfección. En el Campo Experimental Rosario Izapa en 2006, se determinó la tolerancia a desinfectantes de explantes foliares de genotipos de café, mediante la dosis letal media (DL50) y con base en la tolerancia, se definió el desinfectante óptimo para el establecimiento aséptico. La DL50 de hipoclorito de sodio (NaClO), de hipoclorito de calcio (Ca[ClO]2) y la combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Treatments with 2,4-D and ANA resulted in statistically similar partial oxidation, with a higher number of oxidized explants in ITTGj-5; in this genotype, when explants were transported in Gj-3 solution, oxidation decreased. This result is similar to that reported by López-Gómez et al (2011), where they decreased the oxidation of C. arabica explants using ascorbic acid and citric acid, prior to in vitro disinfection. The transport solution had no effect on callogenesis, contrary to the genotype and RGC factor.…”
Section: Callogenesis Inductionsupporting
confidence: 91%
See 1 more Smart Citation
“…Treatments with 2,4-D and ANA resulted in statistically similar partial oxidation, with a higher number of oxidized explants in ITTGj-5; in this genotype, when explants were transported in Gj-3 solution, oxidation decreased. This result is similar to that reported by López-Gómez et al (2011), where they decreased the oxidation of C. arabica explants using ascorbic acid and citric acid, prior to in vitro disinfection. The transport solution had no effect on callogenesis, contrary to the genotype and RGC factor.…”
Section: Callogenesis Inductionsupporting
confidence: 91%
“…On the other hand, in comparison to the first flowering cycle, increasing the immersion time in sodium hypochlorite reduced bacterial contamination to zero. In this regard, López-Gómez et al (2011) found that sodium hypochlorite is effective in controlling in vitro contamination. Depending on the tolerance of the coffee plant to the disinfectant and the time of collection, it is necessary to adjust the dose and exposure time according to the genotype evaluated and its phenology.…”
Section: Induction Of In Vitro Culturesmentioning
confidence: 99%